Origin and evolution of parental magmas associated with Pliocene-Quaternary low-silica volcanism within the Altiplano-Puna Volcanic Complex of northern Chile - González Maurel, Osvaldo Patricio (Department of Geological Sciences, 2021)
The Andean continental arc is built upon the thickest crust on Earth, whose eruption products reflect varying degrees of crustal assimilation. Physical interactions between mafic and felsic magmas for this arc are therefore difficult to recognize due to the differentiation of mantle-derived magma during ascent through the thickened crust and a corresponding lack of erupted primitive lavas. However, a rare concentration of less evolved rocks is located marginal to the partially molten Altiplano-Puna Magma Body (APMB) in the Altiplano-Puna Volcanic Complex of northern Chile, between 21º10'S and 22º50'S. To unravel the petrogenesis of these less evolved eruptives and their spatiotemporal assessment, this work makes use of new major and trace element data, and Sr and Nd isotope ratios of fourteen Pliocene to Quaternary volcanoes. Whole-rock compositional and Sr and Nd isotope data reveal a large degree for compositional heterogeneity (e.g. SiO2 = 53.2 to 63.2 wt%, MgO = 1.74 to 6.08 wt%, Cr = 2 to 382 ppm, Sr = 304 to 885 ppm, 87Sr/86Sr = 0.7055 to 0.7088, and 143Nd/144Nd = 0.5122 to 0.5125). The least evolved products erupted along the periphery of the APMB and are likely equivalent to the replenishing magmas that thermally sustain the large APMB system. Here it is found that the investigated mafic to intermediate eruptives reflect mafic melt injections that underplate the APMB and escape along the sides of the large felsic body to avoid significant compositional modifications during ascent (e.g. La Poruña, San Pedro, Palpana, Chela volcanoes). Investigating these magmas therefore assist in assessing the evolution of the APMB through space and time. Additionally, individual volcanoes demonstrate that contamination of parental melts was caused by different differentiation processes (e.g. magma mixing, fractional crystallization, crustal assimilation) as a function of their spatiotemporal framework relative to the APMB and its melt fraction variation from peripheral (ca. 4 vol%) to central (up to 25 vol%) portions. New insight into the petrological processes that governed the magmatic evolution of La Poruña, one of the centres that exhibit the least evolved eruptions in the area, is presented. La Poruña is a 100 ka scoria cone, composed of pyroclastic material and an extensive basaltic-andesite to andesite lava flow, with magmatic evolution related to the neighbouring larger San Pedro stratovolcano. New petrography, geochemistry and radiogenic isotope data describe a set of porphyritic mafic samples, comprising olivine- and pyroxene-rich rocks, with well-defined major element compositional trends, as well as trace and rare earth element characteristics, that reflect magmatic differentiation at midupper crustal levels. Additionally, magma mixing as well as assimilation and fractional crystallization processes acted on these La Poruña magmas. A remarkable compositional feature is the unusual reversed isotopic behaviour of increasing silica with decreasing 87Sr/86Sr compositions related to later magmatic evolution involving selective assimilation during turbulent ascent at shallow crustal levels prior to eruption, therefore differing from the broadly accepted Central Andean magmatic model. In order to robustly model magma evolution and assimilation at subduction zones such as the Andes, the compositions of parental magmas feeding crustal magma reservoirs need to be defined. Here, new olivine and clinopyroxene oxygen isotope data from six volcanoes located at the margins of the giant APMB is presented, as these data provide robust constraints on parental magma genesis and further contamination processes. Existing olivine and pyroxene  18O values for the Central Andes are highly variable and potentially not representative of sub-arc parental compositions. However, new olivine (n = 6) and clinopyroxene (n = 12)  18O values obtained by Laser Fluorination (LF) analysis display a narrow range, with averages at 6.0‰ ± 0.2 (2σ S.D.) and 6.7‰ ± 0.3 (2σ S.D.), consistent with a common history for the investigated minerals. Additionally, the first in-situ Secondary Ionisation Mass Spectrometry (SIMS) oxygen isotope data for mafic mineral phases from La Poruña and Palpana is presented in order to ensure a robust parental melt δ18O composition, since unlike in LF analysis fractures or mineral/melt inclusions can be avoided. Crystal cores show a density peak at 5.6‰ for both La Poruña and Palpana, whereas rims have either relatively high (6.0‰) or low (5.4‰) peaks. Intra-crystal differences (up to ± 1.1‰) in  18O values between crystal cores and rims accurately record crustal assimilation that postdate cores formation at 13 to 19 km depth. Based on the more robust dataset of LF results, a  18O value for sub-arc, parental melts of ca. 7.0‰ ± 0.2 (2σ S.D.) can be estimated. SIMS core data, on the other hand, indicate a lower, but less well-constrained parental melt value of 6.3‰ ± 0.4 (2σ S.D.).Parental melts feeding the APMB and associated volcanic centres are proposed to form in the felsic continental crust following assimilation of up to 28 vol% high  18O-high 87Sr/86Sr basement rocks by mantle-derived magmas.